Influence of Different Sintering Temperature on Crystal Structure and Electrical Properties of Pr-based Manganites. - Hamzah, Azzam Faiz; Shamsuddin, Suhadir (Enhanced Knowledge in Sciences and Technology, 2023)
: Manganite with monovalent doped of Pr-based, Pr0.75Na0.2Ag0.05MnO3 tend to attract characterization in crystalline structure and electrical properties, such as resistivity. Since Ag+ ions had shown successful substitution and improvement to structural and electrical characteristics which has been seen in previous studies, influence of different temperatures on growth of Pr0.75Na0.2Ag0.05MnO3 manganite compound during sintering process still not yet further investigated. Preparation of manganite samples with high purity of Pr2O3, Na2CO3, Ag2O and MnO2 powders was done using solid state reaction method. Characterization on crystalline structure was done using X-ray diffraction (XRD). The electrical characteristics such as resistivity of the sample was done using 4-point probe equipment method. Meanwhile, bulk density of the sample was run using compact precision balance, then was identified using Archimedes principle, and sample porosity was calculated using standardize formula. XRD analysis depicted that crystalline structure of all the samples were figured out in an orthorhombic structurewith Pnma space group, and an increasing in unit cell volume as increasing of sintering temperature. Based on result of XRD data analysis, it shows increase in bulk density and decrease in porosity as increase in sintering temperature, which can be confirmed through calculation using the samples’ lattice parameter. Based on the data obtained from 4- point probe, it shows that the sample resistivity is reduce with increasing of sintering temperature, which can be proven from the previous research.